Internal Judicial Independence in the EU and Ghosts from the Socialist Past: Why the Court of Justice Should Not Follow AG Pikamäe in Hann-Invest - Nika Bačić Selanec; Davor Petrić (Croatian Yearbook of European Law and Policy)
The editorial comment discusses the preliminary reference and the Opinion of Advocate General Pikamäe in Joined Cases C-554/21, C-622/21 and C-727/21 Hann Invest, which is currently pending before the Grand Chamber of the Court of Justice. In the preliminary reference – the first reference on the state of the rule of law and independence of the judiciary in Croatia – the referring national court questioned whether the Croatian mechanism for ensuring consistency of case law of second-instance national courts and the Supreme Court complies with Article 19(1) TEU. Unlike the AG, this comment argues it does not.